Men's involvement in women's abortion-related care: a scoping review of evidence from low- and middle-income countries. Issue 1 (31st December 2022) - Strong, Joe
Abstract: Men's involvement in abortion is significant, intersecting across the individual, community and macro factors that shape abortion-related care pathways. This scoping review maps the evidence from low- and middle-income countries relating to male involvement, including male abortion providers, in abortion trajectories. Five databases were searched, using search terms, to yield 7493 items published in English between 01.01.2010 and 20.12.2019. 37 items met the inclusion criteria for items relating to male involvement in women's abortion trajectories and were synthesised using an abortion-related care-seeking framework. The majority of studies were conducted in sub-Saharan Africa and were qualitative. Evidence indicated that male involvement was significant, shaping the ability for a woman or girl to disclose her pregnancy or abortion decision. Men as partners were particularly influential, controlling resources necessary for abortion access and providing or withdrawing support for abortions. Denial or rejection of paternity was a critical juncture in many women's abortion trajectories. Men's involvement in abortion trajectories can be both direct and indirect. Contextual realities can make involving men in abortions a necessity, rather than a choice. The impact of male (lack of) involvement undermines the autonomy of a woman or girl to seek an abortion and shapes the conditions under which abortion-seekers are able to access care. This scoping review demonstrates the need for better understanding of the mechanisms, causes and intensions behind male involvement, centring the abortion seeker within this.